Managerial Decision-Making for Process Optimization in CV Jaya Mandiri Textile Operations: Hegemoni Digital - Satrio Arif Budiman; Pri Hermawan (International Journal of Science and Environment (IJSE), 2026)
In today's highly competitive and dynamic business environment, small and medium enterprises (SMEs) must constantly adapt to operational challenges that threaten efficiency and customer satisfaction. CV Jaya Mandiri, an SME based in Malang, engaged in textiles and interior solutions, is currently facing a critical issue of long process times, with customer orders taking up to two weeks from inquiry to final installation. This long waiting period has resulted in customer dissatisfaction, loss of competitiveness, and risks to long-term sustainability. Despite consistent product quality and strong market demand, inefficiencies in the company's internal processes have restricted its ability to deliver convenient service. These challenges highlight the urgent need for process optimization supported by informed managerial decision making. The research aims to address these operational inefficiencies by analyzing the current business processes of CV Jaya Mandiri, identifying root causes of delays, and proposing optimized workflows that reduce process time while aligning with the company's resource capabilities. the research uses a qualitative case study approach. Data is collected through semi-structured interviews with key stakeholders, direct field.